STUDY OF ELECTRICAL INSTALLATION PLANNING AT RACHAEL HOTEL PONTIANAK - Nurhalimah, Nurhalimah (Faculty of Engineering, Universitas Tanjungpura, 2025)
Rachael Hotel Pontianak is a new hotel planned for 8 floors with a building area of 8,998.2 m2. In the early stages of development, this hotel relies heavily on electrical installations, especially lighting and air conditioning installations to support the needs of guests and provide comfort to the facilities that have been provided. This study aims to calculate the need for the number of light points, Air Conditioner capacity, cable cross-sectional area, safety current rating, total power requirements, and cost budget plan (RAB). This research uses literature study, observation and analytical descriptive methods to obtain accurate data and information. In this electrical installation planning, the need for electrical energy to serve the load must be in accordance with the General Requirements for Electrical Installation (PUIL) in 2020, SNI 6197-2020 concerning energy conversion in lighting systems, and SNI 6390-2020 concerning energy conversion of air conditioning systems in buildings. Based on the calculations and analysis that have been carried out, the total electrical load requirement is 286750 Watts with a total lamp requirement of 1577 pieces and a total air conditioning requirement of 167 pieces. From the results of this calculation it is also known that the electric current safety at SDP and MDP uses MCCB components with a panel capacity of 141109.41 VA for SDP 1, and 196243.53 VA for SDP 2, and 337352.94 VA for MDP. The total cost of all electrical installation work is IDR 3,579,439,000.00. This research is expected to provide efficient and effective electrical installation planning for Rachael Hotel, so that it can support the needs of guests and provide comfortable facilities at an optimal cost.